PENGARUH DOSIS DAN WAKTU APLIKASI PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Var. saccharata Sturt) KULTIVAR BONANZA F1 - Achmad Faqih; Dukat Dukat; Trihayana Trihayana (Agroswagati Jurnal Agronomi, 2019)
The aim of this study: (1) To determine the effect the combination of the dose and time application of urea fertilizer on the growth and yield of sweet corn (Zea mays Var.Saccharata Sturt) Cultivars Bonanza F1. (2) To determine the effect the combination of the best dose and time application of urea fertilizer on the growth and yield of sweet corn (Zea mays Var.Saccharata Sturt) Cultivars Bonanza F1. The research was conducted in the village of Susukan Tangkil District of Cirebon - West Java, from September until November, 2018.The research method used was the experimental method with a randomized block design (RAK). This experiment consisted of nine combinations dosage of potassium fertilizer and tillage systems each repeated three times, so there are 27 experimental plots. The combination treatment was tested in the field are: A (urea fertilizer 50 kg/ha and one time application), B (urea fertilizer 50 kg/ha and two time application), C (urea fertilizer 50 kg/ha and three time application), D (urea fertilizer 100 kg/ha and one time application), E (urea fertilizer 100 kg/ha and two time application), F (urea fertilizer 100 kg/ha and three time application), G (urea fertilizer 150 kg/ha and one time application), H (urea fertilizer 150 kg/ha and two time application), I (urea fertilizer 150 kg/ha and three time application).The results showed that: (1) There is a real effect treatment the combination of the dose and time application of urea fertilizer on plant height age of 47 and 54 Days After Planting (DAP), the number of leaves per plant of 47 and 54 Days After Planting (DAP), diameter of age stem of 47 and 54 Days After Planting (DAP), the length and diameter of the cob with husk, and corncob with husk per plot. (2) The combination of dose and time application of the best urea fertilizer from cob weighted per plot in treatment I (urea fertilizer 150 kg/ha and three time application) with weight 9,07 kg equal to 19,33 ton/ha.